Mother-Son Communication about Sex: Exploring Associations with Emerging Adult Sons' Sexual Self-Esteem, Anxiety, and Satisfaction. Issue 1 (2nd January 2022) - Denes, Amanda; Crowley, John P.; Gibson, Laurel P.; Hamlin, Emily L.
Abstract: Parent-child communication about sex and sexuality during adolescence may have long-lasting effects on children's sexual self-concept and sexual health. As such, the present study explored the connection between mother-son communication about sex and sexuality while growing up and emerging adult sons' sexual well-being. The sample consisted of 137 sexually active men between the ages of 18 and 23. The findings revealed that open mother-son communication was negatively associated with sons' sexual anxiety and positively associated with sons' sexual satisfaction, but that sons' sexual self-esteem and anxiety did not account for the association between mother-son communication and sons' sexual satisfaction. These findings provide preliminary evidence that sons' perception that their mother provided an open and non-judgmental communication environment for discussing sex during adolescence is associated with positive sexual outcomes for emerging adult sons later in life. These findings and their implications are explored through the lens of communication privacy management theory.